(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2015)
The paper introduces the study of weighting matrices’ influence on spatial correlations and dynamics of spatial correlation coefficients on the basis of the number of accommodation provided to foreign tourists in accommodation facilities in all subregions (powiaty) of West Pomeranian province (województwo zachodniopomorskie) in the period of 2006-2012. The analysis has been conducted on three types of weight-ing matrices: a) neighbouring matrices, b) matrices of distance between administrative centres of subregions, c) matrices of transport connections (both automotive and railway) as well as on the basis of d) the number of hotels in a particular subregion. The Moran’s global and local correlation coefficients have been calculated and analysed, the coefficients’ dynamics have been analyzed. The study has shown that spatial differentiation for the analysed coefficient has been expressed in the most prominent way by spatial correlation coefficients based on the weighting matrices mentioned in c) and d). On the basis of these results it was concluded that phenomena which show a direct connection to the analysed event present the greatest significance to the analysis of economic phenomena which depend on spatial factors.